Adaptation and validation of the Indonesian family assessment device - Dinda Oktavia Pradina; Fitriani yustikasari Lubis (Program Studi bimbingan Konseling PPs UNM Makassar, 2024)
This research aims to develop a valid and reliable Indonesian version of the Family Assessment Device (FAD). Utilizing a non-experimental quantitative method, the study followed ITC guidelines for adapting the measurement instrument. The adaptation process included forward-backward translation, expert review, and cognitive interviews, before administering the instrument to 226 respondents selected through convenience sampling. The analysis demonstrated good reliability (Cronbach’s alpha = 0.845). Validity was confirmed through expert judgment and a Confirmatory Factor Analysis (CFA) (RMSEA = 0.076; NFI = 0.91; GFI = 0.93; CFI = 0.94). Results showed that of the 53 items, 19 were found to be both valid and reliable.